2022
DOI: 10.1177/10901981221120391
|View full text |Cite
|
Sign up to set email alerts
|

Tackling Oppressive Beliefs and Sexual Violence on College Campuses: Evaluation of an Innovative Theater-Based Intervention

Abstract: Background Sexual violence (SV) prevalence remains high among U.S. college campuses; prevention strategies may benefit from addressing socially oppressive beliefs, including racism, sexism, and heterosexism that all directly link to attitudes and beliefs related to SV. Aims The objective of this study is to evaluate the potential efficacy of a novel student-driven, theater-based intervention in shifting beliefs regarding racism, heterosexism, and SV. Method Data were utilized from paired pre- and posttest surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Philipps et al indicated that students believed in the transformative power of education -of themselves and facultyas a means of improving the medical environment without waiting for social change [30] and Johnsson et al suggested that a semester-long course targeting rst-year students could potentially in uence knowledge, attitudes and behavioural intentions regarding sexual violence and create a more positive campus climate [31] . Given the potential consequences suffered by those exposed to GBV, both the institutions and student welfare organisations should intensify practices and policies to prevent and respond to GBV among university students and also to raise awareness among healthcare workers regarding sexism and homophobia [32] . To help students recognise GBV and learn how to intervene in these situations, more GBV content is needed in prevention education programmes that integrates content pertinent to victimisation risk, perpetration risk and bystander intervention skills [33] .…”
Section: Discussionmentioning
confidence: 99%
“…Philipps et al indicated that students believed in the transformative power of education -of themselves and facultyas a means of improving the medical environment without waiting for social change [30] and Johnsson et al suggested that a semester-long course targeting rst-year students could potentially in uence knowledge, attitudes and behavioural intentions regarding sexual violence and create a more positive campus climate [31] . Given the potential consequences suffered by those exposed to GBV, both the institutions and student welfare organisations should intensify practices and policies to prevent and respond to GBV among university students and also to raise awareness among healthcare workers regarding sexism and homophobia [32] . To help students recognise GBV and learn how to intervene in these situations, more GBV content is needed in prevention education programmes that integrates content pertinent to victimisation risk, perpetration risk and bystander intervention skills [33] .…”
Section: Discussionmentioning
confidence: 99%